PRINCIPLES OF DRUG THERAPY IN NEWBORNS - G.V. Yatsyk; N.D. Odinaeva; I.A. Belyaeva; E.P. Bombardirova; E.I. Tarzyan (Union of pediatricians of Russia, 2011)
The article is devoted to the neonats adequate pharmacotherapy, including use of medications off-label. The authors emphasize the characteristics of a newborn child organism (as a full-term and preterm) that define the distinct processes of pharmacokinetics and pharmacodynamics in the older children. This paper discusses the problem of the optimal route of administration choice, provides basic information about medications used in the most common pathological conditions in newborns. Key words: drug therapy, drugs, newborns, premature infants. (Pediatric pharmacology. - 2011; 8 (6): 50-56).